Mapping and Migration Strategies for Thermal Management in Many-Core Systems - da Silva, Alzemiro Lucas; Martins, André Luís del Mestre; Moraes, Fernando (Symposium on Integrated Circuits and Systems Design (SBCCI), 2020)
New technology nodes enable the integration of billions of transistors in a small silicon area by replicating identical structures, resulting in many-core systems. However, power density may limit the amount of energy the system can consume. A many-core at its maximum performance may lead to safe temperature violations and, consequently, result in reliability issues. Dynamic Thermal Management (DTM) techniques proposals guarantee that many-core systems run at good performance without compromising reliability. In this paper, we review recent DTM works, discussing their limitations, and propose new heuristics for thermal-aware application mapping and migration, using a hardware accelerator that enables temperature monitoring on systems with a large number of processing elements. Results show that using straightforward heuristics, with reactive actions based on runtime temperature monitoring, reduce the peak temperature in high workload scenarios (6.8%), and improve thermal distribution significantly on a large (8×8) many-core system.